Coaching leadership and athlete outcomes in Wushu Taolu: Cross-sectional evidence from elite athletes - Hongren, Zhuang; Hidayat, Taufiq; Prihanto, Junaidi Budi (UIR Press, 2026)
Background: Although coaching leadership has been widely examined in team sports, empirical evidence in individual martial arts, particularly wushu taolu, remains limited. Moreover, previous studies have typically focused on single psychological outcomes, such as motivation or satisfaction, rather than simultaneously examining multiple dimensions. Therefore, it remains unclear whether coaching leadership styles influence intrinsic motivation, training discipline, and athlete satisfaction in individual sport contexts. Objectives: This study aimed to examine the influence of coaching leadership styles on intrinsic motivation, training discipline, and athlete satisfaction among wushu taolu athletes. Methods: A quantitative cross-sectional survey design was employed involving 33 Wushu Taolu athletes from East Java selected through purposive sampling. Data were collected using standardised Likert-scale instruments, including an adapted Leadership Scale for Sports (LSS; 12 items), Intrinsic Motivation Inventory (IMI; 22 items), training discipline indicators (10 items), and Athlete Satisfaction Questionnaire (ASQ; 15 items). All instruments demonstrated acceptable reliability (Cronbach’s α > 0.70). Data were analysed using multiple linear regression at a 5% significance level. Results: The findings revealed that coaching leadership styles did not have a significant effect on intrinsic motivation, training discipline, or athlete satisfaction (p > 0.05). The regression models explained only a small proportion of variance across all dependent variables, indicating very weak predictive power. Conclusion: These results suggest that coaching leadership style alone may not be a strong predictor of psychological outcomes in wushu taolu athletes. Further research with larger samples and additional variables is needed to better understand the determinants of athlete motivation, training discipline, and satisfaction in individual sport contexts.